PELATIHAN PENGOLAHAN AYAM GEPREK BERDASARKAN HAZARD ANALYSIS CRITICAL CONTROL POINT DI SML UMKM CENTRE - Febryola Indra; Nevin Valdira Arkananta (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Healthy food intake has an important role for people to maintain and increase body immunity, especially during the Covid-19 pandemic. Therefore, eating clean and nutritious food can be one of many ways to maintain health. Chicken meat is often people's choice for their dish. In addition to its delicious taste and can be processed into various types of dishes, chicken meat is a healthy food because of its high protein content. Besides food ingredients, cooking methods also play a very important role in health. To maintain good food quality, Hazard Analysis of Critical Control Points (HACCP) system is needed, which is a system of cooking methods that control the condition of food so that it can be consumed safely by consumers. In this online workshop, participants from the SML UMKM Centre community will learn how to prepare and cook geprek chicken by using the HACCP system